Oxidative protein folding by an endoplasmic reticulum-localized peroxiredoxin - Zito, Ester (2018)
Endoplasmic reticulum (ER) oxidation 1 (ERO1) transfers disulfides to protein disulfide isomerase (PDI) and is essential for oxidative protein folding in simple eukaryotes such as yeast and worms. Surprisingly, ERO1-deficient mammalian cells exhibit only a modest delay in disulfide bond formation. To identify ERO1-independent pathways to disulfide bond formation, we purified PDI oxidants with a trapping mutant of PDI. Peroxiredoxin IV (PRDX4) stood out in this list, as the related cytosolic peroxiredoxins are known to form disulfides in the presence of hydroperoxides. Mouse embryo fibroblasts lacking ERO1 were intolerant of PRDX4 knockdown. Introduction of wild-type mammalian PRDX4 into the ER rescued the temperature-sensitive phenotype of an ero1 yeast mutation. In the presence of an H2O2-generating system, purified PRDX4 oxidized PDI and reconstituted oxidative folding of RNase A. These observations implicate ER-localized PRDX4 in a previously unanticipated, parallel, ERO1-independent pathway that couples hydroperoxide production to oxidative protein folding in mammalian cells.